La communication territoriale : constructions d’un champ - Richard Awono (Communiquer)
For almost thirty years, French-speaking scholars (and some researchers in other areas) have taken interest in communication within the local space. However, within this context, “territorial communication” has largely been characterized by some kind of dispersal, and is not well-founded on a theoretical background. How can we explain such a contrast, when new concerns (citizenship, networks, identity crisis…) are putting to question the city and the local space and, finally, communication as a framework for the production of theoretical and public intervention models? From a sociohistorical perspective, this paper revisits the processes of sedimentation in this field, outlining explanations for its “crisis of growth”. A synthesis of new perspectives in the field is also proposed, based on recent research works.